2021
DOI: 10.1017/s026646662100030x
|View full text |Cite
|
Sign up to set email alerts
|

Quantile Double Autoregression

Abstract: Many financial time series have varying structures at different quantile levels, and also exhibit the phenomenon of conditional heteroskedasticity at the same time. However, there is presently no time series model that accommodates both of these features. This paper fills the gap by proposing a novel conditional heteroskedastic model called “quantile double autoregression”. The strict stationarity of the new model is derived, and self-weighted conditional quantile estimation is suggested. Two promising propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Assumption 3 is commonly required for QR processes whose coefficients are functions of a uniform random variable; see Assumption A.3 in Koenker and Xiao (2006) for quantile AR models and Assumption 4 in Zhu and Li (2022) for quantile double AR models.…”
Section: Self-weighted Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Assumption 3 is commonly required for QR processes whose coefficients are functions of a uniform random variable; see Assumption A.3 in Koenker and Xiao (2006) for quantile AR models and Assumption 4 in Zhu and Li (2022) for quantile double AR models.…”
Section: Self-weighted Estimationmentioning
confidence: 99%
“…By assuming that the AR coefficients are functions of a standard uniform random variable, the quantile AR model in Koenker and Xiao (2006) allows for asymmetric dynamic structures across quantile levels; see, e.g., Ferreira (2011) and Baur et al (2012) for various empirical applications of this model. There have been many extensions of the quantile AR model, such as the quantile self-exciting threshold AR model (Cai and Stander, 2008), the threshold quantile AR model (Galvao et al, 2011), and the quantile double AR model (Zhu and Li, 2022). However, as far as we know, the approach of Koenker and Xiao (2006) has not been explored for GARCH-type models.…”
Section: Introductionmentioning
confidence: 99%
“…To capture the time-varying volatility, it is necessary to take the conditional heteroscedasticity into account when a linear model is fitted to financial time series. Among existing conditional heteroscedastic models, the double-autoregressive (DAR) models (Ling, 2004) have recently attracted growing attention, see Cai et al (2013), Li et al (2015), Xu and Zhao (2021), Zhu and Li (2022) and among others. Because it has two novel properties.…”
Section: Introductionmentioning
confidence: 99%
“…Liu, Li, and Kang (2018) investigated the sample path properties of an explosive DAR model. For some recent achievements on the DAR models, we refer to Zhu, Zhang, and Liang (2017), Zhu, Zheng, and Li (2018), Gong and Li (2020), Zhu and Li (2022), among others.…”
Section: Introductionmentioning
confidence: 99%
“…Liu, Li, and Kang (2018) investigated the sample path properties of an explosive DAR model. For some recent achievements on the DAR models, we refer to Zhu, Zhang, and Liang (2017), Zhu, Zheng, and Li (2018), Gong and Li (2020), Zhu and Li (2022), among others. Scholars have found that many financial time series exhibit features such as heavy-tailed, large kurtosis, extreme events and multimodal marginals.…”
Section: Introductionmentioning
confidence: 99%